2014
DOI: 10.1371/journal.pone.0095606
|View full text |Cite
|
Sign up to set email alerts
|

Winter Refuge for Aedes aegypti and Ae. albopictus Mosquitoes in Hanoi during Winter

Abstract: Dengue occurs throughout the year in Hanoi, Vietnam, despite winter low temperatures <10°C. During July 2010 to March 2012, we surveyed monthly for Aedes larvae and pupae in 120 houses in 8 Hanoi districts. Aedes albopictus preferred discarded containers in summer and pupal density drastically decreased in winter. Aedes aegypti preferred concrete tanks and this preference increased in winter. Even in winter, the lowest water temperature found in concrete tanks was >14°C, exceeding the developmental zero point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…In addition, large containers are often difficult to clean more frequently to enable the interruption and prevention of mosquito life-cycle and mosquito production. Less frequent cleaning provides good breeding sites for dengue vector production [3236]. It is thus not the container type as such that is a factor for consideration but rather the combination of container size, their placement, no or poorly fitted lids and low frequency of cleaning that is the combined determinant of Aedes infestation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, large containers are often difficult to clean more frequently to enable the interruption and prevention of mosquito life-cycle and mosquito production. Less frequent cleaning provides good breeding sites for dengue vector production [3236]. It is thus not the container type as such that is a factor for consideration but rather the combination of container size, their placement, no or poorly fitted lids and low frequency of cleaning that is the combined determinant of Aedes infestation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the differences in lifespan and blood‐feeding behavior observed across photoperiods in Ae. aegypti may be an adaptive strategy increasing their survival during winter months in southern Florida where they may remain active (Reiskind and Lounibos , Tsunoda et al ). The longer lifespan during shorter day lengths may sustain the adult through winter conditions, when breeding opportunities may be lacking and immature survival is low.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti encounter photoperiod shifts in their range, each have shown sustained activity to some degree during winter months when day lengths are shortened, particularly Ae. aegypti (Reiskind and Lounibos , Tsunoda et al ). Therefore, one would expect that these two species have evolved sensitivity to photoperiodic fluctuations to better respond to seasonal changes.…”
Section: Introductionmentioning
confidence: 99%
“…The research was conducted in the HMA, Vietnam, which is located at 20°54'34.14"-21°6'22.69" south latitude and 105°42'16.97"-105°56'21.48" east longitude ( Figure 1) with an area of 273.9 km 2 . Vietnam has been experiencing dramatic economic growth since the Doi Moi Policy started in 1986 (Logan, 2005) which has greatly contributed to the rapid urbanization in Hanoi city (Tsunoda et al, 2014), particularly after Hatay province, Vinhphuc province's Melinh district and the four communes of Luongson district, Hoabinh province were merged into the metropolitan area of Hanoi from August 2008 (Hiep, 2014). Therefore, rapid urban development displaced vegetation in many areas, especially in the HMA.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Recent studies have shown that vegetation cover has dramatically decreased in urban districts and some areas of suburban districts because of the incessant urbanization process in the central urban areas and some sub-urban areas of the Hanoi city (Hoang, 2016;Hoang, 2017). Particularly, the Doi Moi Policy since 1986 has greatly contributed to the rapid urbanization process in Hanoi city (Tsunoda et al, 2014). also reported that the construction and rehabilitation of the city's infrastructure and the number of industrial establishments has increased by 4,870,500 m 2 , equivalent to an increase rate of 211,760 m 2 /year since 1990.…”
Section: Spatio-temporal Variation Of Relationship Between Lsts Vegementioning
confidence: 99%